REPAIR AND RETROFITTING OF DETERIORATED REINFORCED CONCRETE STRUCTURES – THREE CASE STUDIES - Al-Gadhib, A.H. (2020)
Concrete is the material most widely used in the construction of reinforced concrete structures including hydraulic structures. There are many diversified applications of reinforced concrete for storage, conveyance and collection of potable water and seawater, irrigation, and wastewater conveyance and treatment. In the Arabian Gulf, the potentially aggressive environment has resulted in premature deterioration of numerous structures in a service performance span of less than a decade. The environment characterized by high humidity and temperature and excessive air/soil borne salinity has resulted in corrosion of the reinforcement and subsequent cracking and spalling of concrete. This paper will address the issues related to repair and strengthening techniques of three reinforced concrete structures. The first case deals with the inspection, assessment and repair strategy of mosque in Dammam. Investigation of structural distress and cracking in a newly constructed seawater conveyance structure and the suggested remedial measures for mitigating the problem are presented in the second case study. Finally, strengthening and monitoring of a distressed reinforced concrete structure that supports a cylindrical tank, using carbon fiber reinforced plates (CFRP) is addressed.